Designing the feedback system for a DC motor to control its angular movement and speed using microcontroller - Raquib, Ahmed; Brian, D’ Rozario (Видавництво Львівської політехніки, 2011)
In today’s world, technology is evolving fast and with expensive and complicated equipments we are able to achieve greater accuracy. This paper presents a simplified and an inexpensive model for replacing more complicated feedback systems like optical encoder using a laser unit, a Light Dependent Resistor (LDR) and a microcontroller in an environment where very high accuracy is not required. Usually it is very difficult to control the speed of a DC motor since it varies with the supplied voltage, but this feedback system can be used to control the movement angle and speed of a DCmotor.
Розробка замкнутої системи для електродвигуна постійного струму для контролю його кутового переміщення та швидкості з використанням мікроконтролера
Keywords: feedback; laser; LDR; microcontroller; angle; speed; encoder; DC motor